IDF Diabetes Atlas: Global estimates for the prevalence of diabetes for 2015 and 2040. (June 2017) - Ogurtsova, K.; da Rocha Fernandes, J.D.; Huang, Y.; Linnenkamp, U.; Guariguata, L.; Cho, N.H.; Cavan, D.; Shaw, J.E.; Makaroff, L.E.
Highlights: Global diabetes prevalence was estimated for 2015 and 2040. In 2015, prevalence of diabetes in adults was estimated to be 8.8%. In 2015, 16.2% of live births were associated with hyperglycaemia in pregnancy. In 2040, the prevalence of diabetes in adults is predicted to rise to 10.4%. Diabetes prevalence continues to rise across the globe. Abstract: Aim: To produce current estimates of the national, regional and global impact of diabetes for 2015 and 2040. Methods: A systematic literature review was conducted to identify data sources on the prevalence of diabetes from studies conducted in the period from 1990 to 2015. An analytic hierarchy process was used to select the most appropriate studies for each country, and estimates for countries without data were modelled using extrapolation from similar countries that had available data. A logistic regression model was used to generate smoothed age-specific estimates, which were applied to UN population estimates. Results: 540 data sources were reviewed, of which 196 sources from 111 countries were selected. In 2015 it was estimated that there were 415 million (uncertainty interval: 340–536 million) people with diabetes aged 20–79 years, 5.0 million deaths attributable to diabetes, and the total global health expenditure due to diabetes was estimated at 673 billion US dollars. Three quarters (75%) of those with diabetes were living in low- and middle-income countries. The number of people with diabetes aged 20–79 years was predicted to rise to 642 million (uncertainty interval: 521–829 million) by 2040. Conclusion: Diabetes prevalence, deaths attributable to diabetes, and health expenditure due to diabetes continue to rise across the globe with important social, financial and health system implications.